2013
DOI: 10.1111/nph.12331
|View full text |Cite
|
Sign up to set email alerts
|

Thirst beats hunger – declining hydration during drought prevents carbon starvation in Norway spruce saplings

Abstract: SummaryDrought-induced tree mortality results from an interaction of several mechanisms. Plant water and carbon relations are interdependent and assessments of their individual contributions are difficult. Because drought always affects both plant hydration and carbon assimilation, it is challenging to disentangle their concomitant effects on carbon balance and carbon translocation. Here, we report results of a manipulation experiment specifically designed to separate drought effects on carbon and water relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
201
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(218 citation statements)
references
References 39 publications
6
201
1
4
Order By: Relevance
“…Moreover, investing carbon into structures (i.e. conduit walls) that would lose their function so readily seems unlikely, especially considering the functional importance of carbon in plant physiology (Mencuccini, 2003;McDowell, 2011;Sala et al, 2012;Hartmann et al, 2013;Charrier et al, 2015;Hartmann, 2015). Finally, the minimal water potential experienced by a plant on a seasonal basis is generally less negative than its C 50 value (Choat et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, investing carbon into structures (i.e. conduit walls) that would lose their function so readily seems unlikely, especially considering the functional importance of carbon in plant physiology (Mencuccini, 2003;McDowell, 2011;Sala et al, 2012;Hartmann et al, 2013;Charrier et al, 2015;Hartmann, 2015). Finally, the minimal water potential experienced by a plant on a seasonal basis is generally less negative than its C 50 value (Choat et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies in the literature are probably due to the different conditions adopted in the experiments. Most of our knowledge comes from studies of adult trees subjected to severe drought stress where water withholding is applied until plant wilting and mortality [19][20][21]. However, it should be noted that responses of young trees growing in natural and anthropic conditions can differ significantly [22].…”
Section: Introductionmentioning
confidence: 99%
“…A proposed flaw of the CSH is that die-back of isohydric plants during prolonged drought events can still be plausible without having exhausted carbon reserves (Sala et al 2010). The ability of plants to move or reallocate carbon reserves during prolonged drought may therefore still provide the necessary energy to survive (Hartmann et al 2013). Drought may therefore not directly lead to reduced carbohydrate reserves and thus tree death (Anderegg et al 2012).…”
Section: Figurementioning
confidence: 99%
“…Sevanto and Dickman (2015) provided an effective solution to moderate the current discrepancies in the CSH as a key mechanism in killing trees. They suggested that it is to gain a better understanding of the actual reallocation and transport of stored carbon to those plant tissues 1986;McDowell et al 2010;McDowell et al 2011;Hartmann et al 2013;Sevanto et al 2014;Anderegg et al 2015a). Since the time during which a tree is subjected to dangerous hydraulic thresholds could be more important than plant thresholds per se, it is possible to be even more precise in applying such tree die-back models (McDowell et al 2013; see also Choat et al 2012).…”
Section: Figurementioning
confidence: 99%